Evolutionary game analysis of ecological cooperation in a supply chain ecosystem under government supervision - Luan, Mengmeng; Yin, Linsen; Ye, Mengting; Huang, Lufei (Frontiers in Physics, 2025)
IntroductionThe development of digital technology and upgrading of consumer service demand have led to profound changes in the supply chain, gradually forming a supply chain ecosystem and transforming inter-enterprise cooperation into ecological cooperation. Amidst complex international landscapes and industrial transformation, the role of government has garnered significant attention. Thus, enhancing ecological cooperation in the supply chain during the new development stage and clarifying the government’s role constitute critical research topics.MethodsWe analyze strategies of governments, suppliers, and manufacturers using a three-party evolutionary game model. The ideal event is defined within this model, and key influences on the dynamic evolutionary process are examined. A sensitivity analysis of selected parameters is rigorously conducted.ResultsOur findings demonstrate that: (1) The government significantly promotes ecological cooperation among supply chain enterprises and can adjust system equilibrium by modulating the subsidy coefficient and regulatory costs. (2) Greater eco-sensitivity enhances advantages in eco-cooperation. (3) Establishing reasonable compensation fees between enterprises ensures effective eco-cooperation. (4) A company’s cost investment in eco-cooperation critically influences its engagement in such collaboration.DiscussionThe study confirms the government’s pivotal role in facilitating supply chain ecological cooperation through policy instruments. Eco-sensitivity, inter-firm compensation mechanisms, and cost investments are identified as decisive factors for successful collaboration. Sensitivity analysis further validates the robustness of these parameters in shaping evolutionary outcomes.